2020
DOI: 10.1007/s00521-020-05362-z
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid bio-inspired algorithm and convolutional neural network for automatic lung tumor detection

Abstract: In this paper, we have proposed a hybrid bio-inspired algorithm which takes the merits of whale optimization algorithm (WOA) and adaptive particle swarm optimization (APSO). The proposed algorithm is referred as the hybrid WOA_APSO algorithm. We utilize a convolutional neural network (CNN) for classification purposes. Extensive experiments are performed to evaluate the performance of the proposed model. Here, pre-processing and segmentation are performed on 120 lung CT images for obtaining the segmented tumore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Moreover, SqueezeNet and ResNet are executed together for the classification of lung nodule. Vijh et al [20] introduced the hybrid bio-inspired Whale optimization algorithm with adaptive particle swarm optimization (WOA-APSO) for feature selection with convolutional neural network for classification of lung cancer nodules. The Wiener filter has been applied to eliminate noise from CT image in preprocessing.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, SqueezeNet and ResNet are executed together for the classification of lung nodule. Vijh et al [20] introduced the hybrid bio-inspired Whale optimization algorithm with adaptive particle swarm optimization (WOA-APSO) for feature selection with convolutional neural network for classification of lung cancer nodules. The Wiener filter has been applied to eliminate noise from CT image in preprocessing.…”
Section: Related Workmentioning
confidence: 99%
“…[17,18,28] requires to improve the detection accuracy. The study [21,23] was based on an imbalanced dataset while other research works [19,20,26,30,31] are based on a complex model.…”
Section: Related Workmentioning
confidence: 99%
“…Few popular optimization algorithms are artificial bee colony (ABC) [27] [71] [72] [73], particle swarm optimization (PSO) [28], whale optimization algorithm (WOA) [29], genetic algorithm (GA) [30], adaptive particle swarm optimization [31], cuckoo search algorithm [32], grey wolf optimization [33], cat swarm optimization [34], and lion optimization algorithm [35]. These optimization algorithms provide the optimal global solution for the selected set of features through exploitation and exploration [36,37].…”
Section: Related Workmentioning
confidence: 99%
“…Vijh et al [ 89 ] suggested a hybrid bionic approach that combines the benefits of whale optimization and adaptive particle swarm optimization. In this method, 120 lung CT images were preprocessed and segmented using CNN to obtain segmented nodules in tumor and non-tumor areas.…”
Section: Practical Applications Of Convolutional Neural Network In Tumor Diagnosismentioning
confidence: 99%